Baseline medication load and long-term outcomes in COVID-19-hospitalized patients: results of the AUTCOVSTUDY - Alexandra Graf; Berthold Reichardt; Christine Wagenlechner; Christine Wagenlechner; Pavla Krotka; Denise Traxler-Weidenauer; Denise Traxler-Weidenauer; Denise Traxler-Weidenauer; Michael Mildner; Julia Mascherbauer; Clemens Aigner; Johann Auer; et al. (Frontiers in Public Health)
IntroductionLimited data are available on long-term morbidity and mortality after hospitalization for coronavirus disease 2019 (COVID-19). In this registry-based study, we investigated long-term mortality and morbidity following hospitalization for COVID-19 and examined associations with baseline medication load.MethodsData were provided by the Austrian Health Insurance Funds on hospitalized COVID-19 patients in 2020 and matched controls. The primary outcome was mortality. Secondary outcomes included mortality conditional on survival of initial COVID-19 hospitalization and re-hospitalization.ResultsThe median follow-up was 600 days. A total of 22,571 patients aged >18 were hospitalized in Austria in 2020 due to COVID-19. The risk of mortality was significantly higher with polypharmacy. With the exception of the youngest age group (19–40 years), patients receiving antiepileptics, antipsychotics, or iron supplements, erythropoiesis-stimulating agents, vitamin B12, or folic acid in the year before hospitalization were significantly associated with a higher risk of mortality (all p < 0.001). For patients with prescribed non-steroidal anti-inflammatory drugs (NSAIDs) and other anti-inflammatory drugs, significantly increased survival was observed (all p-values <0.001). Patients had a higher medication load than the control population. Long-term mortality and the risk of re-hospitalization for any reason were also significantly higher among patients.DiscussionAntipsychotics and antidepressants appear to be underrecognized in identifying patients at risk for severe outcomes after hospitalization for COVID-19.